L’inflation disciplinaire et conceptuelle dans les sciences paléoenvironnementales - Magali Watteaux; Gérard Chouquer (Développement Durable et Territoires)
At the end of a historiographical and epistemological research on the disciplines at the crossroads of History, Archeology, Geography and naturalistic sciences, the authors proposed a reasoned inventory of 152 disciplinary titles observed in this research field. In this article they specifically deal with the situation of paleoenvironmental sciences where there is also a profusion of disciplinary names. In doing so, they provide a critical reading of the concept of environment, ubiquitous in research. Finally, they support the view that disciplinary inflation reflects the emergence of a vast field of research : the rediscovery of the Earth and the complexity of its legacies.